Don't monkey with the forest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Guenon monkeys play an important role in the regeneration of the rain forest in southern Cameroon. These small monkeys eat a lot of fruit and excrete the seeds. It turns out that monkey-passed seeds not only get more widely distributed but also...